Persepsi Mahasiswa Terhadap Penerapan Manajemen Pembelajaran Berbasis Proyek di Perguruan Tinggi Islam - Iwan Sopwandin; Isep Nendri Rostiana (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Project-based learning can encourage students to think actively and creatively in developing their ideas so that this opportunity will give a pleasant impression in the learning process. This research aims to analyze student perceptions regarding the implementation of project-based learning management at the Sekolah Tinggi Ilmu Tarbiyah Az Zahra Tasikmalaya. This research uses a combination method of sequential exploratory models, for sampling techniques using Purposive Sampling techniques with the following sampling techniques: 1) observation; 2) documentation study; and 3) surveys. Qualitative data is analyzed through the stages of data condensation, data presentation, drawing conclusions, while quantitative data is analyzed through descriptive statistics. The research results show that: 1) project-based learning management in the education and training management course includes: a) planning, namely syllabus delivery, module preparation and lecture orientation; b) implementation, namely the preparation of modules that are carried out at each lecture meeting and implementation of training; c) evaluation, carried out at each meeting after the preparation of the module and at the end when it has entered the training implementation material or before the training is carried out; d) reporting, this activity is carried out after students and their groups have finished carrying out the training; 2) student perceptions of the implementation of project-based learning management in the education and training management management course are in the good category (45% good and 55% very good); and 3) Student responses to the ability of lecturers to teach using the project-based learning model are in the good category (35% good and 65% very good).